DEVELOPMENT OF HOUSING AND COMMUNAL SPHERE IN EUROPEAN COUNTRIES - K. A. Ivanov (Модернизация, инновация, развитие)
In many European countries, local authorities are largely independent of the central powers of the country and more dependent on the population that elects them. In the western housing and communal system, both private and public firms may work. In apartment buildings, management decisions are most often made within the framework of an association of tenants (a legal entity), while execution of the decisions are entrusted to a professional management companies under contracts. State-owned vertically integrated industry monopolies are rejected, competition is encouraged.